2D melting of confined colloids with a mixture of square and triangular order. (25th October 2018) - Jungmann, R M; Pereira, P C N; Apolinario, S W S
Abstract: We implement Brownian dynamics to investigate the melting processes of colloidal particles confined isotropically and interacting via a potential which can be tailored in a repulsive–attractive–respulsive fashion as the interparticle distance increases. The stable configurations of such a system is composed of a large diversity of structures, which includes quasicrystalline, triangular, square, and mixed orderings, as well as the presence of fringes and holes, which are located, respectively, at the border and interior of the clusters. Our simulations demonstrate that during the melting process particles are able to swing between different micro phases. This intermediary stage, present in a finite range of temperature, precedes the melting in all cases investigated and is different from the hexatic phase of the KTNHY framework. We also test the fringes stability and find it to be higher than the one found in compact clusters. Finally, we show that, at the high temperature regime, the system loses its angular ordering while still preserves its radial interparticle confinement, which, ultimately, causes the proliferation of small subclusters.